Meaning as a Normative Stance - Petit, Arnaud (Université d'Ottawa / University of Ottawa, 2017)
In the past few years, the claim that meaning is normative has grown increasingly suspect and many powerful arguments have been developed against its interpretation in terms of (1) conditions of correct use, (2) prescriptions and (3) rule-following. In the first essay of my thesis, I discuss the precise arguments that have been invoked by Paul Boghossian and by Kathrin Glüer and Asa Wikforss against the latter interpretation. In the second essay, I turn towards the two other interpretations of the normativity of meaning, as they are discussed by Anandi Hattiangadi and by Daniel Whiting. My main strategy in both of these essays is to show that the possibility of following a rule, like the existence of conditions of correct use, depends on our ability — and our willingness — to adopt a normative stance. That is to say, I defend the normativity of meaning by showing (i) that we (as human beings) are not indifferent as to how things are done or how words are used and (ii) that the notions of “rule-following” and of “conditions of correct use” are ways to express that fact. In the first essay, I attempt to clarify what I mean by adopting a normative stance — and following a rule — by linking them with the notions of understanding and of intelligent behaviour. In the second essay, I rather insist that conditions of correct use can be explained in terms of appropriateness or of fittingness with the circumstances. As such, I put myself in a position to criticize the traditional unfolding of that notion and to further articulate my idea of a normative stance.
Keywords: Philosophy